2013
DOI: 10.1007/s12031-013-0013-9
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of Tumor Necrosis Factor Alpha and MicroRNA-155 in Immature Rat Model of Status Epilepticus and Children with Mesial Temporal Lobe Epilepsy

Abstract: Recently, the role of inflammation has attracted great attention in the pathogenesis of mesial temporal lobe epilepsy (MTLE), and microRNAs start to emerge as promising new players in MTLE pathogenesis. In this study, we investigated the dynamic expression patterns of tumor necrosis factor alpha (TNF-α) and microRNA-155 (miR-155) in the hippocampi of an immature rat model of status epilepticus (SE) and children with MTLE. The expressions of TNF-α and miR-155 were significantly upregulated in the seizure-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
76
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 40 publications
8
76
0
1
Order By: Relevance
“…Kan et al (2012) profiled the miRNAs changes in human TLE [17]. Our previous experiments supported the role of inflammation-related miRNAs (miR-146a, -155, -21, and -132) and brain-specific miRNAs (miR-124 and -134) in the pathogenesis of MTLE in immature rat models and children [20,29,30].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Kan et al (2012) profiled the miRNAs changes in human TLE [17]. Our previous experiments supported the role of inflammation-related miRNAs (miR-146a, -155, -21, and -132) and brain-specific miRNAs (miR-124 and -134) in the pathogenesis of MTLE in immature rat models and children [20,29,30].…”
Section: Discussionsupporting
confidence: 74%
“…Intra-peritoneal pilocarpine administration Clinical information on children with MTLE and controls has been described previously [20].…”
Section: Experimental Animalsmentioning
confidence: 99%
“…Up-regulated miRNAs includes miR-21, miR-23a, miR-23b, miR-24, miR-27a, miR-27b, miR-34a, miR-126, miR-132, miR-140, miR146a, miR-152, miR-210 and miR-212 while downregulated miRNAs includes miR-33, miR-138, miR-139, miR-187, miR-190, miR-218a, miR-301a, miR-551b and miR-935. Among the up-regulated miRNAs only three were mentioned in three human experiments, which are miR-21, miR-132 and miR-146a [30][31][32]. Of note, miR-134 is also an important microRNA that is up-regulated during epilepsy, which is only profiled in one human experiment of Jimenez-Manteos et al [23].…”
Section: Micrornas Profiling In Different Time Phases After Sementioning
confidence: 99%
“…Recent researches showed that inflammationrelated miRNAs, including miRs (146a, 21, 181a, 221, and 222), have a close relationship with multiple CNS diseases, including mesial temporal lobe epilepsy (MTLE) [13][14][15] , and ischemic injuries [16,17] . Seventy percent of experimentally-detected miRNAs are found in mamm-alian brain tissues [18] ; among these, at least seven brain-enriched miRNAs including miRs (124, 134, 9, 132, and 138) have been described.…”
Section: Research Highlightmentioning
confidence: 99%
“…Our research group is vigorously working to understand the mechanisms of many CNS diseases including meningitis [25][26][27] , intractable epilepsy [13,15,28] , and ischemic injuries [22] . Recent studies have shown that brain inflammation is an important factor contributing to almost all CNS diseases and activation of microglia is considered to be neuroinflammation hallmark.…”
Section: Research Highlightmentioning
confidence: 99%